Pengembangan Alat Evaluasi Berbasis Literasi Sains untuk Mengukur Kemampuan Literasi Sains Siswa SMP/MTs Bertema Gejala Alam - Khabibah, Elva Arista Nur; Rusilowati, Ani; Supriyadi, Supriyadi (UPEJ Unnes Physics Education Journal, 2019)
The purposes of this research are develope a scientific literacy evaluation instrument, determine the validity, reliability and describe characteristic of scientific literacy assessment instrument and the profile of students' scientific literacy abilities. The research design uses R & D (Research and Development) with a sampling technique used simple random sampling. The subject of this research was conducted in class VII of SMP & MTs in Brebes. The results showed that the scientific literacy evaluation instrument was stated fulfill the content validity with very valid category, equability validity with high category and was stated reliable with a reliability value of 0.89 in the first product trials and 0.92 in the last product trial. The characteristics of this scientific literacy evaluation instrument have proportion levels of difficulty that are proportional. The content of the science literacy category has a proportion of 27% for science as a body of knowledge, a way of investigating, a way of thingking, and 19% for interaction between science, environment, technology, and society. The profile of students scientific literacy show the mastery of science literacy is still low that is below 60%.